2022
DOI: 10.1126/sciimmunol.abk0018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TLR4 during vaccination boosts MAdCAM-1 + lymphoid stromal cell activation and promotes the aged germinal center response

Abstract: The failure to generate enduring humoral immunity after vaccination is a hallmark of advancing age. This can be attributed to a reduction in the germinal center (GC) response, which generates long-lived antibody-secreting cells that protect against (re)infection. Despite intensive investigation, the primary cellular defect underlying impaired GCs in aging has not been identified. Here, we used heterochronic parabiosis to demonstrate that GC formation was dictated by the age of the lymph node (LN) microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 80 publications
(106 reference statements)
2
20
0
Order By: Relevance
“…Our observations that there are no significant age-related defects in class-switch recombination are concordant with previous in vivo studies by (Dailey et al, 2001) and ex vivo studies on aged mouse follicular B cells by (Russell Knode et al, 2019), but are not consistent with other studies that reported reduced class-switch recombination in aged splenic mouse B cells when stimulated in vitro with CD40L and IL-4 (Frasca et al, 2004(Frasca et al, , 2007. This may suggest some conjoined; B cells from young mice displayed a significant defect in mounting a GC response in an aged lymph node compared to those in a young environment (Denton et al, 2022). This, together with data from our adoptive transfer experiment, suggests that the age of the lymphoid environment, rather than the age of B cells, contributes more to defects in GC formation during ageing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our observations that there are no significant age-related defects in class-switch recombination are concordant with previous in vivo studies by (Dailey et al, 2001) and ex vivo studies on aged mouse follicular B cells by (Russell Knode et al, 2019), but are not consistent with other studies that reported reduced class-switch recombination in aged splenic mouse B cells when stimulated in vitro with CD40L and IL-4 (Frasca et al, 2004(Frasca et al, , 2007. This may suggest some conjoined; B cells from young mice displayed a significant defect in mounting a GC response in an aged lymph node compared to those in a young environment (Denton et al, 2022). This, together with data from our adoptive transfer experiment, suggests that the age of the lymphoid environment, rather than the age of B cells, contributes more to defects in GC formation during ageing.…”
Section: Discussionsupporting
confidence: 78%
“…When transgenic B cells from a young SW HEL mouse were transferred into young and aged recipient mice, very few of the transferred HEL + B cells were detectable in the aged recipient mice, compared to those transferred into a young environment. These observations match those from heterochronic parabiosis studies, where the circulatory systems of young and aged mice are surgically conjoined; B cells from young mice displayed a significant defect in mounting a GC response in an aged lymph node compared to those in a young environment (Denton et al, 2022 ). This, together with data from our adoptive transfer experiment, suggests that the age of the lymphoid environment, rather than the age of B cells, contributes more to defects in GC formation during ageing.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Inflammation affected EFR induction in an intrinsic manner, as functional Toll-like receptor (TLR) signaling axes either through MyD88/TRIF or TLR2/4/Unc93b induced optimal activation of the NF-kB c-Rel:IRF4 pathway (Suppl. (Denton et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Given the above results, we asked how B cell fate dynamics and EFR-derived antibody functionality is affected by repeated antigen exposure with or without TLR agonist provision. For that, all mice were primed with influenza and LPS to ensure equivalent initiation of LN activation (Denton et al, 2022), followed by two additional boosts with antigen alone (Ag Boosted), or antigen plus LPS (Ag+LPS Boosted) or LPS alone (LPS Boosted) as a control (Fig. 8a).…”
Section: Reconstitution Of Efrs During Influenza Immunization Through...mentioning
confidence: 99%